Dzielimy się doświadczeniemEffect of temperature on blood viscosity. The importance of hypothermia in cardiac surgery and myocardial infarction - Wasilewski, Jarosław; Głowacki, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The paper presents the interrelation between temperature and blood viscosity and the clinical significance of this phenomenon in the cardiac surgery in the hypothermia condition and intravascular cooling adjunctive to percutaneous coronary intervention for acute myocardial infarction.